The Prognostic Significance and Potential Mechanism of Ferroptosis-Related Genes in Hepatocellular Carcinoma - Li, Wenli; Liu, Jun; Zhang, Dangui; Gu, Liming; Zhao, Hetong (Frontiers in Genetics, 2022)
Ferroptosis exerts a pivotal role in the formation and dissemination processes of hepatocellular carcinoma (HCC). The heterogeneity of ferroptosis and the link between ferroptosis and immune responses have remained elusive. Based on ferroptosis related genes (FRGs) and HCC patients from The Cancer Genome Atlas (TCGA), International Cancer Genome Consortium (ICGC) and Gene Expression Omnibus (GEO) cohorts, we comprehensively explored the heterogenous ferroptosis subtypes. The genetic alterations, Consensus-Cluster and Survival analysis, immune infiltration, pathway enrichment analysis, integrated signature development and nomogram building were further investigated. Kaplan-Meier plotter confirmed a statistically differential probabilities of survival among the three subgroups. Immune infiltration analysis showed there were clear difference in types of immune cells infiltration, the expression of PD-L1 and the distribution of TP53 mutations among the three clusters. Univariate Cox regression analysis, random survival forests and multivariate Cox analysis were used to identify the prognostic integrated signature, including MED8, PIGU, PPM1G, RAN, SNRPB. Kaplan–Meier and time-dependent receiver-operating characteristic (ROC) curves revealed the satisfactory predictive potential of the five-gene model. Subsequently, a nomogram was established which combined the signature with clinical factors. The nomogram including the ferroptosis-based signature was conducted and shown some clinical net benefit. These results facilitated an understanding of ferroptosis and immune responses for HCC.